A comparative analysis of internet banking in Malaysia and Thailand - Mohamad Rizal Abdul Hamid; Hanudin Amin; Suddin Lada; Noren Ahmad (Bathurst, N.S.W. : Charles Sturt University, 2007)
The purpose of this paper is to compare the internet banking system in Malaysia and Thailand. Using comparison as the theoretical base, secondary data were used to determine the differences between both countries with respect to Internet banking. Analysis of the data indicates that both nations are dissimilar in providing basic services offered by their commercial banks. Belief on lack of effort on educating the consumers toward internet banking further affected the usability of internet banking in both countries. This study hopes to contribute to the literature on internet banking in Malaysia and Thailand.